Mortality and morbidity 1 year after stopping a remote patient management intervention: extended follow-up results from the telemedical interventional management in patients with heart failure II (TIM-HF2) randomised trial. Issue 1 (January 2020) - Koehler, Friedrich; Koehler, Kerstin; Prescher, Sandra; Kirwan, Bridget-Anne; Wegscheider, Karl; Vettorazzi, Eik; Lezius, Susanne; Winkler, Sebastian; Moeller, Volker; Fiss, Gunnar; Schleder, Judith; Koehler, Magdalena; et al.
Summary: Background: The Telemedical Interventional Management in Heart Failure II (TIM-HF2) trial showed that, compared with usual care, a structured remote patient management (RPM) intervention done over 12-months reduced the percentage of days lost due to unplanned cardiovascular hospitalisations and all-cause death. The aim of the study was to evaluate whether this clinical benefit seen for the RPM group during the initial 12 month follow-up of the TIM-HF2 trial would be sustained 1 year after stopping the RPM intervention. Methods: TIM-HF2 was a prospective, randomised, multicentre trial done in 43 hospitals, 60 cardiology practices, and 87 general practitioners in Germany. Patients with heart failure, New York Heart Association functional class II or III, and who had been hospitalised for heart failure within 12 months before randomisation were randomly assigned to either the RPM intervention or usual care. At the final study visit (main trial), the RPM intervention was stopped and the 1 year extended follow-up period started, which lasted 1 year. The primary outcome was percentage of days lost due to unplanned cardiovascular hospitalisations and all-cause mortality. Analyses were done using the intention-to-treat principle. This trial is registered with ClinicalTrials.gov, number NCT01878630 . Findings: Between Aug 13, 2013, and May 12, 2017, 1538 patients were enrolled (765 to the remote patient management group and 773 to the usual care group) in the main trial. 671 of 765 patients in the remote patient management group and 673 of 773 in the usual care group completed the main trial and started the extended follow-up period up to 1 year later. In the extended follow-up period, the percentage of days lost due to unplanned cardiovascular hospital admissions and all-cause mortality did not differ significantly between groups weighted mean 5·95% [95% CI 4·59–7·31] in the RPM group vs 6·64% [95% CI 5·19–8·08] in the usual care group [rate ratio 0·79; 95% CI 0·78–1·21]). However, when data from the main trial and the extended follow-up period were combined, the percentage of days lost due to unplanned cardiovascular hospitalisation or all-cause death was significantly less in patients allocated to the RPM group (382 [50%] of 765; weighted mean 9·28%; 95% CI 7·76–10·81) than in the UC group (398 [51%] of 773; 11·78%; 95% CI 10·08–13·49; ratio of weighted average 0·79; 95% CI 0·62–1·00; p=0·0486). Interpretation: The positive effect of our RPM intervention on morbidity and mortality over the course of the main trial was no longer observed 1 year after stopping the RPM intervention. However, because the TIM-HF2 trial was not powered to show significance during the extended follow-up period, our results are exploratory and require further research. Funding: German Federal Ministry of Education and Research.